Tahun Yubileum: Maknanya bagi Keluarga Kristiani dalam Terang Pemikiran Paus Fransiskus dan Julie Hanlon Rubio - Christiawan, Stevanus Devi (Lux et Sal, 2025)
Proclaimed by Pope Francis through the Bull Spes Non Confundit, the Jubilee Year 2025 adopts the theme Pilgrims of Hope, offering the universal Church a unique opportunity to renew spiritual life and reaffirm the social and missionary dimensions of Christian faith. This article examines the pastoral and spiritual significance of the Jubilee, particularly in the context of Christian family life, drawing upon the insights of Julie Hanlon Rubio and the teachings of Pope Francis. The approach taken views the family as a distinctive locus theologicus , where the spirituality of the Jubilee manifests in daily living—not merely as devotional expression but as a concrete form of social participation and faith witness. The article elaborates on six key characteristics of the Jubilee Year—pilgrimage, the holy door, reconciliation, prayer, profession of faith, and acts of charity—and integrates them into the lived experience of Christian families. Rubio’s perspective highlights family faith practices as ethical means of shaping spiritual habitus, fostering spiritual growth, interpersonal relationships, and social engagement. Simultaneously, Pope Francis’s vision of synodality and his call for a “Church that goes forth” inspire families to become missionary communities that embody and transmit faith, hope, and love to others. Accordingly, the Jubilee Year is understood not merely as a liturgical celebration, but as a dynamic process of pastoral renewal. It positions the family as both subject of evangelization and witness to divine mercy.